CONSUMER PURCHASE INTENTION TOWARD INSTANT NOODLES - Aiman bin Mohammed; Wan Rusni binti Wan Ismail; Norliana binti Hashim; Nor Hafizah binti Mazlan (International Journal of Accounting, Finance and Business, 2022)
The purpose of this study was to identify the relationship between the factors ofconvenience (CO), product attributes (PA), subjective norms (SN) and perceived risk (PR)toward consumer purchase intention toward instant noodles. The population in this study wasconsumers who have experience purchasing and consuming instant noodles in Malaysia. 465respondents were gathered, and the collected data were analyzed using SPSS. The relationshipbetween the factors of convenience (CO), product attributes (PA), subjective norms (SN) andperceived risk (PR) toward consumer purchase intention toward instant noodles has beenanalyzed by using Spearman's Rho correlation as the data was not normally distributed. Thefindings show that convenience, product attributes, and subjective norms have a significantrelationship between consumers' purchase intention toward instant noodles. Nevertheless,consumer perceived risk towards instant noodles recorded an insignificant relationship withpurchase intention.